2022
DOI: 10.3389/fchem.2021.821806
|View full text |Cite
|
Sign up to set email alerts
|

Pyroligneous Acids of Differently Pretreated Hybrid Aspen Biomass: Herbicide and Fungicide Performance

Abstract: The pyroligneous acids (PAs) of woody biomass produced by torrefaction have pesticidal properties. Thus, PAs are potential alternatives to synthetic plant protection chemicals. Although woody biomass is a renewable feedstock, its use must be efficient. The efficiency of biomass utilization can be improved by applying a cascading use principle. This study is novel because we evaluate for the first time the pesticidal potential of PAs derived from the bark of hybrid aspen (Populus tremula L. × Populus tremuloide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…40 The effects were consistent with that of PA, which is mainly explained by the complex compositions of dissolved biochars such as humic acid-like substances, small molecule phenols, and organic acids. PAs, one of the by-products simultaneously derived from ACS Environmental Au biomass pyrolysis for biochar production, 28,29 containing similar chemical components with the dissolved biochars (Figure S1), would be responsible for the hormesis on ARG transfer, which will be discussed in the following section.…”
Section: Hormesis Of Pa On the Conjugative Transfer Of Plasmid Rp4mentioning
confidence: 99%
See 4 more Smart Citations
“…40 The effects were consistent with that of PA, which is mainly explained by the complex compositions of dissolved biochars such as humic acid-like substances, small molecule phenols, and organic acids. PAs, one of the by-products simultaneously derived from ACS Environmental Au biomass pyrolysis for biochar production, 28,29 containing similar chemical components with the dissolved biochars (Figure S1), would be responsible for the hormesis on ARG transfer, which will be discussed in the following section.…”
Section: Hormesis Of Pa On the Conjugative Transfer Of Plasmid Rp4mentioning
confidence: 99%
“…Increasing strategies are recommended to alleviate ARG pollution in agricultural soils, such as aerobic composting or anaerobic digestion of manure and sludge before use, , inactivation of ARGs and antibiotic resistant bacteria from the reclaimed water before irrigation, vermiculture, , phage therapy, and soil amendment (e.g., biochar, calcined eggshell, and nanomaterials) applications. ,, Among them, soil amendments, , which may fight against ARGs already existing in soils, have attracted increasing attention because of their efficiencies and convenient implementation . Pyroligneous acids (PAs) derived from biomass pyrolysis, as multifunctional soil amendments with long history, can decrease soil salinity and pH, , regulate bacterial community, kill plant pathogenic fungi and bacteria, and promote crop growth and grain yield . Our recent studies first demonstrated that PA amendment can reduce ARG levels in soils grown with vegetable Brassica, regardless individual application or combined with biochar amendment. , Similarly, another research also reported that the combined treatment of bamboo biochar and distilled PA showed significant synergistic effects on alleviating ARG proliferation in municipal solid waste composts .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations